Drying of Antioxidant Composite Materials based on Table Beet - Zhanna Petrova; Yuriy Snezhkіn; Vadym Pazyuk; Kateryna Samoilenko (Energy Engineering and Control Systems)
Reduction in the cost of energy in the food industry is an important challenge today due to increased prices. Drying process of plant material refers to the complex energy-intensive processes. Solution of this problem is the development of drying methods that would reduce energy consumption by the process. In the drying of plant material, another major factor is the quality indicators of the finished product, which depend mainly on the drying technology. Therefore, in the Institute of Technical Thermal Physics, energy-efficient drying modes of plant material that made it possible to reduce energy consumption at the drying process and to preserve the biologically active substances of the feedstock were developed. Research is devoted to developing energy-efficient drying modes of antioxidant materials based on table beet that provide betanin saving by 95 % and reducing energy consumption by 49 %. Today in Ukraine, there are not enough companies processing plant materials in powder, thus preserving the quality of the feedstock.